Prognostic Markers in Head and Neck Cancer Patients Treated with Nivolumab - Nishikawa, Daisuke (Cancers (Basel), 2018)
To investigate whether peripheral blood biomarkers predict the outcome of anti-PD-1 antibody treatment for head and neck squamous cell carcinoma (HNSCC). Patients treated with nivolumab for platinum-refractory recurrent or metastatic HNSCC were retrospectively reviewed. Fifty-three patients treated between April 2017 and March 2018 were included in the study. The median progression-free survival (PFS) and overall survival (OS) were 2.5 and 8.7 months, respectively. In the univariate analysis, performance status (PS) ≥ 3, relative neutrophil count ≥ 0.65, relative lymphocyte count ≥ 0.17, and relative eosinophil count (REC) ≥ 0.015 were significantly associated with both PFS and OS. On multivariate analysis, PS ≥ 3 and REC ≥ 0.015 were significantly associated with PFS and OS. Low REC and poor PS were independent poor prognostic factors for both PFS and OS in patients with recurrent or metastatic HNSCC treated with nivolumab.